Is There a Relationship Benefit in Credit Ratings? - Mählmann, Thomas (Review of Finance, 2011)
Abstract This paper shows that firms with longer rating agency relationships have better credit ratings, conditional on observables. The paper also finds that (1) controlling for observables, firms with longer relationships, while having higher average ratings, do not have lower default rates, (2) relationship benefits are larger among firms with a greater incentive to game their information supplied to agencies or to pressure agencies into giving higher ratings, and (3) investors demand a (price) discount on bonds sold by relationship firms and the correlation between bond yield spreads and ratings is decreasing with relationship length. In sum, the evidence is inconsistent with first-order credit quality explanations but rather supports a “learning-to-gaming” and an “adverse incentives” story.